The physiological and ecological characteristics of some phytoremediation plants for wastewater treatment: a review - Sri Sumiyati; Anik Sarminingsih; Budi Warsito (Institute of Advanced Engineering and Science, 2026)
Phytoremediation has emerged as an effective method for mitigating heavy metal contamination in waterways. This study synthesizes literature to assess the physiological and ecological characteristics enhancing the efficiency of five plant species traditionally recognized for their phytoremediation potential: Napier grass (Pennisetum purpureum), Phragmites australis, Typha spp., Pistia stratiotes, and Eichhornia crassipes. A systematic review methodology was utilized, focusing on data from Proquest, EBSCO, and Scopus, prioritizing studies based on pollutant absorption capacities, publication quality, and recency. Key parameters examined include the identification of plant species, growth conditions, pollutant absorption efficiency, ecological roles, and physiological characteristics. Phragmites australis is noted for its nutrient uptake and sediment stabilization, while Eichhornia crassipes demonstrates high heavy metal absorption and rapid growth. Pistia stratiotes effectively removes heavy metals and enhances water quality, and Typha spp. aids in nutrient removal while providing habitat. Napier grass contributes to biomass production and soil stabilization. The integration of these species into wastewater treatment systems not only improves water quality but also fosters sustainability and ecological health. This study emphasizes the potential utility of these plants in environmental management initiatives, highlighting the necessity for careful monitoring to mitigate associated ecological risks.